Public Interest as a Category of Administrative and Legal Science - Tetiana Evgeniivna Kaganovska; Iryna Anatiliivna Pakhomova; Vladyslav Olegovich Neviadovskyi; Artem Oleksandrovych Yefremov (Universidad Hemisferios, 2022)
The article examines the content and features of the public interest as a category of administrative and legal science. The main features of public interest are clarified, namely: (i) it is a set of certain needs (values); (ii) there may be needs of the whole society, as well as its groups or individual citizens; (iii) is provided at the initiative of the directly interested subject or public administration; (iv) these interests are recognized by the state, can be normatively fixed; (v) aimed at ensuring human rights and freedoms; (vi) are provided by subjects of public administration. It is established that the content of public interest as an administrative-legal category follows from the essence of general interest and is individualized by the content of administrative-legal relations. Public interest is defined as a set of certain needs (values) of a person or society, aimed at ensuring and protecting human rights and freedoms and implemented in the activities of public administration. It is established that the public interest reflects the interests of society as a whole or an individual, but its needs may become significant for society as a whole. The types of public interests are distinguished depending on the sphere of realization, territory of distribution and number of persons expressing public interest.